Students' Perceptions of Wordwall Learning Media in Improving their Speaking Skills - Hammam Ukhrowi; Heni Novitasari (Jurnal Indonesia Sosial Sains, 2026)
Speaking skills are a major challenge for Indonesian EFL students, often caused by teacher-centered methods and lack of interactive media. This leads to low participation and motivation in speaking activities. Game-based platforms like Wordwall present a promising alternative to create more engaging learning experiences. This research investigates the students’ perceptions of the use of Wordwall learning media in improving English speaking skills. The study employed a descriptive qualitative design involving 40 tenth-grade students at Vocational High School Nurul Islam who had previously used Wordwall in English speaking lessons. Data were collected through questionnaires and documentation and analyzed using the Miles and Huberman Interactive Model consisting of data collection, data reduction, data display, and conclusion drawing. The findings indicate that students generally have positive perceptions of Wordwall as a learning medium. Students perceived Wordwall as easy to use, attractive, and beneficial in supporting English learning activities. The platform helped students improve vocabulary mastery and pronunciation while increasing learning motivation and classroom participation. Nevertheless, its contribution to speaking fluency, grammatical accuracy, and speaking confidence was perceived as moderate. The findings suggest that Wordwall can serve as an effective supplementary learning medium for speaking instruction when integrated with communicative classroom activities and teacher guidance. This study contributes to the growing body of literature on game-based learning by providing insights into students’ perceptions and experiences regarding the implementation of Wordwall in Indonesian EFL classrooms.